2019
DOI: 10.1016/j.ijpx.2019.100025
|View full text |Cite
|
Sign up to set email alerts
|

3-O-ethyl-l-ascorbic acid: Characterisation and investigation of single solvent systems for delivery to the skin

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 44 publications
5
45
1
4
Order By: Relevance
“…The solubility parameters of the solvent mixtures were estimated by the Van-Krevelen and Hoftyzer approach using Molecular Modelling Pro ® software (Version 7.0.8, 2016, Norgwyn Montgomery Software, Inc., North Wales, PA, USA), as explained previously [12]. Solubility studies were conducted at 32 ± 1 • C and samples were analysed using the previously reported and validated HPLC method [5].…”
Section: Miscibility Solubility Parameter Calculation and Solubilitmentioning
confidence: 99%
See 4 more Smart Citations
“…The solubility parameters of the solvent mixtures were estimated by the Van-Krevelen and Hoftyzer approach using Molecular Modelling Pro ® software (Version 7.0.8, 2016, Norgwyn Montgomery Software, Inc., North Wales, PA, USA), as explained previously [12]. Solubility studies were conducted at 32 ± 1 • C and samples were analysed using the previously reported and validated HPLC method [5].…”
Section: Miscibility Solubility Parameter Calculation and Solubilitmentioning
confidence: 99%
“…All formulations were prepared to contain EA 2% (w/w), because neat solvents containing EA at this concentration were previously reported to promote penetration of the active across pig skin [5]. Permeation studies were conducted in full thickness porcine ear skin in vitro, using Franz-type cells of a diffusion area of approximately 1 cm 2 and were followed by mass balance studies.…”
Section: Porcine Skin Permeation and Mass Balance Studies Of Eamentioning
confidence: 99%
See 3 more Smart Citations